HUBUNGAN PENGETAHUAN, NILAI DAN SIKAP KELUARGA DENGAN PEMBERIAN DUKUNGAN PADA PASIEN GANGGUAN JIWA DI POLIKLINIK PSIKIATRI RSJ PROF. DR. V. L. RATUMBUYSANG PROPINSI SULAWESI UTARA - Makaghee, Marshaly; Bawotong, Jeavery; Rottie, Julia (e-NERS)
Abstract: Mental disorder is a disturbance in the way of thinking, will, emotion and action, where individuals are not able to adjust themselves to others and the environment. Familiy is the closest to the patient, can be a big influence for the healing process of mental patients, which can contribute to patient care, either at home or in the hospital, support provided has several functions : informational support, appraisal support, instrumental support and emotional support. To provided support needed good knowledge, positif value and good attitude within any family members of patients in order to apply to the purpose. Purpose of this study was to find correlation between knowledge, value and family attitude in providing support to patients with mental disorders. Number of samples obtained as many as 40 people, using purposive sampling technique. Study design used is descriptive correlatif with Cross Sectional approach. The result of chi square statistical test obtained Ï = 0,002 for family knowledge, Ï = 0, 014 for the value of the family and Ï = 0,007 for a family attitude. The third factor has a value ofÂ  Ï <Î±, in other words there isÂ  an influence between knowledge, value and family attitude in supporting the mental disorder patients at the Psychiatric Clinic RSJ Prof. Dr. V. L. Ratumbuysang North Sulawesi Province. Conclusion of this study is the knowledge, values and attitudes of the family had an influence on the motivation of the family in providing support for inspection at mental disorder patients. Suggesting that health is expected to be more active providing counseling to families of the patients in the context of patient care, in order to prevent the recurrence of a mental disorder. Key Words: Mental Disorder, Family Support, Knowledge, Value and Attitude. Â  Â  Abstrak: Gangguan jiwa merupakan gangguan dalam cara berpikir, kemauan, emosi dan tindakan dimana individu tidak mampu menyesuaikan diri sendiri, orang lain serta lingkungan. Keluarga merupakan pihak yang terdekat dengan pasien yang dapat memberi pengaruh yang besar bagi proses penyembuhan pasien gangguan jiwa, yang mendukung dalam setiap proses perawatan pasien, baik di Rumah Sakit maupun di rumah, seperti dapat mengurangi stress dan meningkatkan penyesuaian diri pasien terhadap kejadian-kejadian dalam kehidupan. Dalam memberikan dukungan diperlukan pengetahuan yang baik, nilai yang positif dari anggota keluarga serta sikap yang positif dari tiap anggota keluarga. Tujuan dari penelitian ini adalah untuk mengetahui hubungan antara pengetahuan, nilai dalam keluarga serta sikap keluarga dengan pemberian dukungan pada pasien gangguan jiwa. Jumlah sampel yang didapatkan yaitu sebanyak 40 orang responden, dengan menggunakan teknik purposive sampling. Desain penelitian yang digunakan adalah deskriptif korelatif dengan pendekatan Cross Sectional. Hasil Uji statistic Chi-Square yang dilakukan, diperoleh nilai Ï = 0,002 untuk pengetahuan keluarga, Ï = 0, 014 untuk nilai dalam keluarga dan Ï = 0,007 untuk sikap keluarga. Ketiga factor tersebut memiliki nilai Ï < Î±, dengan kata lain terdapat hubungan antara pengetahuan, nilai dan sikap keluarga dengan pemberian dukungan pada pasien gangguan jiwa di Poliklinik Psikiatri RSJ Prof. Dr. V. L. Ratumbuysang Propinsi Sulawesi Utara. Kesimpulan/saran dari pelaksanaan penelitian ini yaitu diharapkan kepada para petugas kesehatan agar dapat lebih meningkatkan pengetahuan yang perlu diketahui keluarga dalam perawatan pasien gangguan jiwa di rumah agar dapat mencegah kekambuhan kembali penderita gangguan jiwa. Kata kunci: Gangguan jiwa, Dukungan Keluarga, Pengetahuan, Nilai, Sikap.